MEMPERCANTIK ATAU MERUSAK: ANALISIS KONSEP TEOLOGI TUBUH DAN PERSPEKTIF TERHADAP MAKE UP BAGI GENERASI ALFA - Elsadai Sofiana Kawengian; Nontje M. Timbuleng (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2025)
This research explores the phenomenon of make-up usage among generation alpha children, who are growing up amidst intense digital culture exposure, examined through the lens of the Theology of the Body. As a generation exposed to social media from an early age, generation alpha faces the pressure of digital beauty standards that risk shifting the understanding of the body from a sacred subject to a mere aesthetic object. Using a descriptive-qualitative analysis method through theological and sociological approaches, this article examines whether early-age make-up use serves as a means of self-expression that beautifies or instead damages the meaning of the body as Imago Dei (Image of God). The analysis shows that the Theology of the Body views the body not merely as outward matter but as a sacrament reflecting the divine presence. Therefore, the use of make-up for generation alpha requires balanced pastoral guidance and theological education to maintain the integrity of bodily dignity, ensuring that outward beauty does not overshadow the essence of the body as a holy gift from God.